1989
DOI: 10.1148/radiology.170.3.2644658
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma: earlier discovery and increased detection.

Abstract: To document the earlier discovery and increased detection of renal cell carcinoma, the authors reviewed cases of renal cell carcinoma detected at their institution during 1974-1977 and 1982-1985, with particular emphasis on renal tumors 3.0 cm or smaller. Only 5.3% (four of 75) of renal cell carcinomas found during 1974-1977 but 25.4% (31 of 122) found during 1982-1985 were 3.0 cm or smaller, an increase of almost five times. Of the small tumors in the 1982-1985 group 96.7% (30 of 31) were incidentally discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
8

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(105 citation statements)
references
References 0 publications
1
95
0
8
Order By: Relevance
“…25,33 Hematuria was the main complaint in the symptomatic cases, in 47% of the cases in this study, and only one patient showed the classical triad (hematuria, back pain and palpable mass) that in the past was seen in 10% of cases 5 and is now only rarely seen. 30 In the last few years there has been an increase in the detection of incidental tumors, 18 directly related to the use of imaging exams, especially ultrasonography and CT scans. 18,34,35 The "internist's tumor" 36 can thus be renamed the "radiologist's tumor", 30 because of the identification of RCC at its early stages, thereby increasing the apparent disease prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25,33 Hematuria was the main complaint in the symptomatic cases, in 47% of the cases in this study, and only one patient showed the classical triad (hematuria, back pain and palpable mass) that in the past was seen in 10% of cases 5 and is now only rarely seen. 30 In the last few years there has been an increase in the detection of incidental tumors, 18 directly related to the use of imaging exams, especially ultrasonography and CT scans. 18,34,35 The "internist's tumor" 36 can thus be renamed the "radiologist's tumor", 30 because of the identification of RCC at its early stages, thereby increasing the apparent disease prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…30 In the last few years there has been an increase in the detection of incidental tumors, 18 directly related to the use of imaging exams, especially ultrasonography and CT scans. 18,34,35 The "internist's tumor" 36 can thus be renamed the "radiologist's tumor", 30 because of the identification of RCC at its early stages, thereby increasing the apparent disease prevalence. 37 These tumors are frequently small and found in routine examinations and evaluations of other diseases, 38,39,40 with greater incidence among younger males and females with a useful working life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the growing use of diagnostic imaging tests by ultrasound and CT, more renal AMLs can be detected at random (16). Another characteristic feature of AMLs is abundant fat tissue (17), easily detected by CT or MR images (18).…”
Section: Imagingmentioning
confidence: 99%
“…2). An angiogram revealed a single right renal artery and a mildly hypervascular the 1980s [3]. The natural history of malignant cyst transformations is unknown.…”
mentioning
confidence: 99%